Sex Differences in Clinical Characteristics and Brain MRI Change in Patients With Wilson’s Disease in a Chinese Population - Li, Xiaohu; Feng, Zhiqiang; Tang, Wei; Yu, Xuen; Qian, Yinfeng; Liu, Bin; Li, Xiaoshu; Yang, Renmin; Yu, Yongqiang (Frontiers in Physiology, 2018)
Background: Wilson’s disease (WD) is an inborn copper metabolism disease. Sex differences in clinical features of WD patients have been reported; however, the effect of sex on brain MRI is still unclear, especially for Chinese WD patients. Therefore, we aimed to examine sex differences in clinical correlates and MRI in WD patients in a Chinese Han population. Methods: 535 WD patients were enrolled and underwent MRI scanning. These patients were subdivided by the clinical symptoms, Kayser-Fleischer (K-F) rings, laboratory tests and sex. The mean age of onset and diagnosis, disease latency, localization of brain MRI lesions and the level of copper metabolism were compared between male and female patients. Results: The neuropsychiatric form (452, 84.5%) was the most subtype. Compared to female patients, male patients had a higher percentage in three clinical forms: neuropsychiatric form (263, 58.2%), hepatic form (41, 59.4%), and presymptomatic form (10, 71.4%). In the neuropsychiatric form, male patients had the earlier age of onset and definitive diagnosis, and shorter time of disease latency than female patients. In the hepatic form, more male patients showed the ventricular widening than female patients (14/41 vs. 3/28; p<0.05). Conclusions: Our findings suggest sex differences in the percentage of three clinical forms. Meanwhile, the mean age of onset, diagnosis and the disease latency favoring females. Only in the hepatic form, there was a sex difference in the ventricular widening.